Analisis Penerapan Manajemen Strategik dan Pengaruhnya terhadap Kinerja Karyawan di PT Karya Giri Palma - Adhelia Putri Zainuri; Sari Andayani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Strategic management plays a crucial role in ensuring the operational sustainability and competitiveness of PT Karya Giri Palma, a manufacturing company specializing in springbed and furniture production. In an increasingly competitive market environment and amid ongoing production challenges, the company is required to implement well-structured and adaptive strategic management practices. This study employs a qualitative research approach to explore the implementation of strategic management within the organization and to identify obstacles that arise during its integration into daily operational activities. Data were collected through in-depth observations and interviews to obtain a comprehensive understanding of managerial practices and employee involvement. The findings reveal that the active participation of both management and employees in the formulation and implementation of strategies significantly contributes to improved employee motivation, higher productivity levels, and enhanced work quality. Strategic alignment between organizational goals and employee roles encourages a stronger sense of responsibility and commitment among employees. However, several challenges remain, particularly in cross-divisional coordination and the consistent execution of strategies at the operational level. Therefore, this study recommends strengthening interdepartmental communication, optimizing the use of management information systems, and enhancing human resource capabilities through continuous training. These findings may serve as a valuable reference for similar manufacturing companies seeking to optimize strategic management practices in order to achieve sustainable performance and long-term competitiveness.